(3GdCYdGb GdNWjQI aj PcQ CeQGA GdTGe hGdLRjQIs - (3eMeO Hf Ydj Hf EHQGgje GdCfUGQj GdMdHj Ke GdeUQj, CHhYHO Gddg YR GdOjf, GHf TOGO,J (B684 (3g` s ((3YHO GdhGSY Hf GdTgjQ HGdbGVi bQG? s)
(3ChdgG (B:s
(3jbhd GdYHO GdabjQ GdZfi Hf eMeO Hf Ydi GHf TOGO , GdMeO ddg GdPi bU ef CfHGA GdQSd eG KHJ Hg aDGO QShdg hHYO , aEfg deG MddJ HeUQ hTedfi ef CfYGe ehdGfG GdSdWGf Cf CVY cJGHkG CPcQ ajg eaUdkG cd LfO s
(3BNQgG (B:s
(3hCeG bdYI fLe hJhai Gdedc GdYRjR hUGQJ Edi hdOg Gdedc GdfGUQ ajeG UGQ ef GdHdGO , heG RGdJ ai edcg Edi Cf EfbVJ GdOhdI hCNQHJgG GdJJQ s
(3HgG fXGe GdJYbjHIs
(3HChdgG bQGAGJ hJedcGJ CbOegG SfI (B1027(3g`s
(3ai GdeYgO fSN CNQi , HQbe (B43 (3, (B893 (3JGQjNs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs